KIT-dependent and KIT-independent genomic heterogeneity of resistance in gastrointestinal stromal tumors: TORC1/2 inhibition as salvage strategy - Mühlenberg, Thomas Eike Markus; Ketzer, Julia; Heinrich, Michael C.; Grunewald, Susanne; Marino-Enriquez, Adrian; Trautmann, Marcel; Hartmann, Wolfgang; Wardelmann, Eva; Treckmann, Jürgen; Worm, Karl; Bertram, Stefanie; Herold, Thomas; et al. (Molecular cancer therapeutics, 2019)
Sporadic gastrointestinal stromal tumors (GIST), characterized by activating mutations of KIT or PDGFRA, favorably respond to KIT inhibitory treatment but eventually become resistant. The development of effective salvage treatments is complicated by the heterogeneity of KIT secondary resistance mutations. Recently, additional mutations that independently activate KIT-downstream signaling have been found in pretreated patients—adding further complexity to the scope of resistance. We collected genotyping data for KIT from tumor samples of pretreated GIST, providing a representative overview on the distribution and incidence of secondary KIT mutations (n = 80). Analyzing next-generation sequencing data of 109 GIST, we found that 18% carried mutations in KIT-downstream signaling intermediates (NF1/2, PTEN, RAS, PIK3CA, TSC1/2, AKT, BRAF) potentially mediating resistance to KIT inhibitors. Notably, we found no apparent other driver mutations in refractory cases that were analyzed by whole exome/genome sequencing (13/109). Using CRISPR/Cas9 methods, we generated a panel of GIST cell lines harboring mutations in KIT, PTEN, KRAS, NF1, and TSC2. We utilized this panel to evaluate sapanisertib, a novel mTOR kinase inhibitor, as a salvage strategy. Sapanisertib had potent antiproliferative effects in all cell lines, including those with KIT-downstream mutations. Combinations with KIT or MEK inhibitors completely abrogated GIST-survival signaling and displayed synergistic effects. Our isogenic cell line panel closely approximates the genetic heterogeneity of resistance observed in heavily pretreated patients with GIST. With the clinical development of novel, broad spectrum KIT inhibitors, emergence of non-KIT-related resistance may require combination treatments with inhibitors of KIT-downstream signaling such as mTOR or MEK.
Gesehen am 09.12.2019